A Psychological Critique of Knowles’ Andragogy as a Theory of Learning - Ian Moll (AS: Andragoška Spoznanja)
The theory of andragogy has had considerable purchase amongst adult educators over time. Although it differs in emphasis in its north American and eastern European poles, the theory derives from a psychological distinction between the way that adults and children learn. Defining the theory in the terms of its most influential theorist, Malcolm Knowles, this article develops a critique of andragogy in relation to mainstream theories of learning. Knowles argues adults are psychologically disposed to “immediate”, life-orientated learning, whereas children’s learning has a “postponed” developmental orientation to the future. However, this particular adult-child distinction has little veracity or credibility when considered against mainstream theories of learning. Rather than a purported cleavage between the learning of adults and children, it seems that Knowles is actually driving at a distinction between non-formal and formal teaching methods, and that this is a better way of thinking about the distinctiveness of adult education than any insights that “andragogy” may have to offer.